Taphonomic variation in vascular remains from Mesozoic non-avian dinosaurs - M. H. Schweitzer; W. Zheng; E. Dickinson; J. Scannella; A. Hartstone-Rose; P. Sjövall; J. Lindgren (Scientific Reports)
Abstract The identity and source of flexible, semi-transparent, vascular-like components recovered from non-avian dinosaur bone are debated, because: (1) such preservation is not predicted by degradation models; (2) taphonomic mechanisms for this type of preservation are not well defined; and (3) although support for molecular endogeneity has been demonstrated in select specimens, comparable data are lacking on a broader scale. Here, we use a suite of micromorphological and molecular techniques to examine vessel-like material recovered from the skeletal remains of six non-avian dinosaurs, representing different taxa, depositional environments and geological ages, and we compare the data obtained from our analyses against vessels liberated from extant ostrich bone. The results of this in-depth, multi-faceted study present strong support for endogeneity of the fossil-derived vessels, although we also detect evidence of invasive microorganisms.